KEDUDUKAN JABATAN DAN AKTA PEJABAT PEMBUAT AKTA TANAH DALAM SENGKETA DI PERADILAN TATA USAHA NEGARA - Bambang Yunarko (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2013)
Pejabat Pembuat Akta Tanah merupakan pejabat umum yang bertugas membantu Kepala Kantor Pertanahan dalam melaksanakan kegiatan tertentu dalam pendaftaran tanah. Pejabat Pembuat Akta Tanah berwenang membuat akta yang berkaitan dengan perbuatan hukum mengenai hak atas tanah dan hak milik atas bantuan rumah susun. Pejabat Pembuat Akta Tanah merupakan pejabat tata usaha negara, namun akta yang dibuatnya bukanlah merupakan keputusan tata usaha negara sehingga tidak menjadi obyek sengketa di Pengadilan Tata Usaha Negara.A land deed officer is a general officer who has function to help the head officer of the land office in the level of municipality, in regard to the registration of the land. The land deed officer has an authority to produce a legal certificate which is related to a legal acts for rights of the land and flats. Also the officer of land deed is the officer of administrative, however the deed or a certificate of the land which is legalized by the land deed officer is not product of administrative. Therefore it cannot be disputed in Administrative Court.